Aetio-pathology of Epistaxis: A Study of 165 Cases (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Epistaxis or nose bleeding is an intensely common problem all over the world. It affects almost all age groups of people. In human life span, up to 60% of the people will experience epistaxis and only 6% of them seek medical attention.Objectives: To find out the aetio-pathological factors of epistaxis and to observe its outcome.Materials and Methods: This cross-sectional observational study was carried out in the Department of Otolaryngology and Head-Neck Surgery (ENT) at Combined Military Hospital (CMH), Chattogram from January 2013 to December 2016 and in CMH, Dhaka from January 2017 to July 2019 among 165 patients who reported with complaints of nose bleeding to the ENT Outpatient Department or Emergency unit of the aforementioned hospitals. The cases were diagnosed on the basis of history, clinical examination, radiological and laboratory investigations and the data regarding aetiopathological factors, outcome of the epistaxis were recorded.Results: The study reveals that the incidence of epistaxis was 14.32% (165 of 1152 patients) with male predominance 70% with a mean age of incidence at 34.44 years. High incidence was noted in the month of December (25) and February (18) where average temperature was 25.03°C and average humidity 79.06% which were typical in cold weather. Low incidence was found in April (7) and October (7) where range of temperature was 26.5°C to 28.2°C and humidity 75.16% to 78.90% respectively. Majority 65.45% reported with bilateral bleeding, 75.76% reported first time, 70.90% of cases had anterior epistaxis. The commonest aetiology was trauma 40% and nasal mass was found in 7.27% cases. Majority 87.27% of patients were treated successfully by nonsurgical/non-interventional method.Conclusion: Epistaxis is found in all age groups, mostly observed in the third and fourth decade of life with male predominance. With a proper diagnosis, prompt intervention and vigilance, epistaxis can be treated conservatively in maximum cases.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 156-159